Methane Plume Emissions Associated With Puget Sound Faults in the Cascadia Forearc. (29th December 2021) - Johnson, H. Paul; Merle, Susan G.; Bjorklund, Tor A.; Hautala, Susan L.; Baumberger, Tamara; Walker, Sharon L.; Liu, Junzhe; Ward, Nicholas D.; Wang, Chenyu
Abstract: Methane gas plumes have been discovered to issue from the seafloor in the Puget Sound estuary. These gas emission sites are co‐located over traces of three major fault zones that fracture the entire forearc crust of the Cascadia Subduction Zone. Multibeam and single‐beam sonar data from cruises conducted in years 2011, 2018, 2019, 2020, and 2021 identified the acoustic signature of 349 individual bubble plumes. Dissolved CH4 gas from the plumes combines to elevate seawater methane concentrations of the entire Puget Sound estuary. Fluid samples from adjacent terrestrial hot springs and deep‐water wells surrounding the estuary contain a helium‐3 isotope signature, suggesting a deep fluid source located near the underlying Cascadia Subduction Zone plate interface. However, limited data from this pilot study suggest that Puget Sound seawater emission sites lack both similar chemical isotope signatures and elevated thermal anomalies that would be expected from association with a deep plate‐interface reservoir. A shallow reservoir within the Holocene sediments that cover the older Puget Sound basement with horizontal transfer to the thinly covered Alki Point and Kingston Arch anticlines is also a possibility, as has been suggested for other methane seep areas. The existence of vigorous marine methane plumes arising from areas of thin sediment cover associated with deeply penetrating forearc fault zones but presenting no thermal or chemical anomalies found in other similar forearc environments, remains an unresolved paradox. Plain Language Summary: Puget Sound is a large inland sea located in western Washington State where seawater circulation is dominated by vigorous tidal forcing from the North Pacific Ocean. The deep Puget Sound is the largest estuary in North America measured by contained water volume and the second largest estuary after Chesapeake Bay in terms of area. Shipboard sonar images have revealed approximately 349 bubble plumes of methane gas and fluid rising from the seafloor of the estuary. Large clusters of bubble plume sites are concentrated over the major regional fault zones that penetrate the western North American plate beneath Puget Sound, including the South Whidbey Island Fault, the Seattle Fault, and the Tacoma Fault Zones. Although the forearc Puget Basin is surrounded by terrestrial hot springs and water wells that show a clear chemical isotope signature of fluid arising from the underlying Cascadia Subduction Zone plate interface, based on our limited sampling there is currently no evidence for similar chemical or temperature anomalies in the Puget Sound plumes and the source of the methane bubble plumes is still unidentified. Key Points: Extensive methane bubble plumes have been discovered on the Puget Sound seafloor The emission sites of these plumes are associated with major fault zones that penetrate the Cascadia forearc Dissolved methane arising from the plumes is mixed throughout the estuary by tides and local mixing